2021
DOI: 10.29392/001c.24944
|View full text |Cite
|
Sign up to set email alerts
|

Extent and causes of increased domestic violence during the COVID-19 pandemic: community health worker perspectives from Kenya, Bangladesh, and Haiti

Abstract: BackgroundEmerging data, media reports, and anecdotal evidence suggest that domestic violence (DV) has increased during the COVID-19 pandemic. However, more detailed data are needed on the magnitude, forms, and causes of DV during COVID-19 in different contexts worldwide. We sought to contribute such evidence from the perspective of community health workers (CHWs) in low-middle income countries in three different regions of the world. MethodsWe conducted phone surveys with female and male CHWs from September-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Moreover, we found that the continental distribution of articles on IPV seems to be concentrated around Ethiopia. Thus, Ethiopia 5 (50%) (Gebrewahd et al, 2020;Shewangzaw Engda et al, 2022;Shitu et al, 2021;Tadesse et al, 2022;Teshome et al, 2021), Nigeria 2(20%) (Fawole et al, 2021;Ojeahere et al, 2022), Kenya 1(10%) (Gottert et al, 2021), Tunisia 1(10) (Sediri et al, 2020), and Zimbabwe 1(10%) (Turner et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, we found that the continental distribution of articles on IPV seems to be concentrated around Ethiopia. Thus, Ethiopia 5 (50%) (Gebrewahd et al, 2020;Shewangzaw Engda et al, 2022;Shitu et al, 2021;Tadesse et al, 2022;Teshome et al, 2021), Nigeria 2(20%) (Fawole et al, 2021;Ojeahere et al, 2022), Kenya 1(10%) (Gottert et al, 2021), Tunisia 1(10) (Sediri et al, 2020), and Zimbabwe 1(10%) (Turner et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are studies (Adejimi et al, 2014;Centers for Disease Control and Prevention, 2015) that reported females as perpetrators too (Macassa et al, 2022). Though IPV predated the SARS-CoV-2 outbreak, the pandemic became a significant addition to the predictors of this social menace for various reasons (Duncan et al, 2020;Gottert et al, 2021;Jarnecke and Flanagan, 2020;John et al, 2020;Mazza et al, 2020; United Nations Women [UNW], 2020a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, financial losses during and after the outbreak not only increased the financial burden but also resulted in anger, frustration, and excessive substance use [12] . Further, statistics suggest that there was an increase in domestic violence during COVID-19 due to increased stress/tension related to economic hardship and childcare [13] . Also, it has been reported that restrictions in movement due to COVID-19 in the early stages resulted in frequent, severe, and dangerous violence at home [14] .…”
Section: Introductionmentioning
confidence: 99%